End-User Training for Sci-Tech Databases - Ellis, Mount (Routledge, 2020)
This book, first published in 1990, analyses how to train end-users to search with both natural language and controlled vocabularies in the sciences, describes a planning assessment for implementing end-user searching in a sci-tech organization, examines how the scientists at a major industrial research organization have begun to do more online searching with the encouragement of the information center, and explores the proactive role that medical libraries have taken in training health care professionals to search MEDLINE.